Trajectories of success and/or distress: protocol for an observational cohort study investigating changing psychological distress among emerging Ecuadorian adults over a year. Issue 12 (20th December 2021) - Paz, Clara; Osejo-Taco, Gabriel; Evans, Chris
Abstract : Introduction: Emerging adulthood is a period of instability with changes in personal relationships and often a series of job changes before life trajectories clarify and more lasting decisions are possible. These changes often produce distress, and they might explain why most of the symptoms that impact the individual's mental health throughout their lives appear at this stage, although full-blown disorders are often only diagnosed subsequently. The objective of this study is to analyse the intraindividual changes in psychological distress and health-related quality of life in both student and non-student emerging adults over 1 year. Between-individual differences in variability will be analysed and life events will be recorded to identify possible associations. Methods and analysis: Participants will be emerging adults (18–29 years of age) students and non-students. The primary outcome will be psychological distress measured using the Clinical Outcomes in Routine Evaluation-Outcome Measure and the secondary outcome will be health-related quality of life measured by the EuroQol five-dimension-three-level. Sociodemographic and life events will be recorded. Information will be collected using an online survey.Analyses, described in a data analysis plan with the registration, will check the psychometric properties of the measures, describe the distribution of scores on the outcome measures, their relationship to group and other demographic variables and how they change over the seven assessment points across a year and explore any relationship between scores and life events. Ethics and dissemination: This study received ethical approval by the Comité de Ética y Bioética (Ethics and Bioethics Committee) of the Universidad de Las Américas, Quito-Ecuador (2020-0807). Results will be published in peer-reviewed journals and presented at relevant meetings. Brief reports of these publications will be disseminated using social media to reach the community and private or public organisations interested in emerging adults. Trial registration number: NCT04596345